Reactivity of anti-tegument monoclonal antibodies with target epitopes in different worm tissues and develonmental stages of schistosoma mansoni - Suda Riengrojpitak (2018)
Sixteen monoclonal antibodies (MABs) were selected for their reactivity with adult schistosome tegument. The distribution of target epitopes in different tissues of the adult and in various developmental stages was investigated by indirect immunofluorescence. The distinct patterns of reactivity of the MABs permitted their classification into 9 groups. The distribution of epitopes in larvae, particularly 3 h schistosomula, generally mirrored that in adults. A change in distribution of epitopes coincided with transformation from cercaria to schistosomulum providing a marker for this process. Two MABs reacted with surface membranes of intact cercariae, and 5 with the surfaces of intact 3 h schistosomula. The target epitopes of these 5 MABs were present in the tegument of adults, but not accessible externally. These observations suggest masking of antigens, not shedding, in the course of development. Indeed, no MAB reacted with intact lung or liver worms unless they were damaged. Three MABs reacted with membranes of the tegument and most other tissues, implying properties in common. Evidence for shared functions between epithelia was provided by the reactivity of 2 MABs with the tegument and protonephridia. Eight MABs bound both to the tegument and its cell bodies. Since the latter contains the machinery for protein synthesis, it is difficult to explain why 5 MABs bound to the tegument alone. Little cross-reactivity was found with the tissues of the tapeworm Hymenolepis, rather more with the closely related Schistosoma japonicum. It was concluded that tegument antigens are to a degree tissue specific but definitely not stage specific. © 1989, Cambridge University Press. All rights reserved.